Upregulated hypoxia inducible factor-1alpha and -2alpha pathway in rheumatoid arthritis and osteoarthritis. - Giatromanolaki, A; Sivridis, E; Maltezos, E; Athanassou, N; Papazoglou, D; Gatter, K; Harris, A; Koukourakis, M (BioMed Central, 2003)
The pathogenesis of rheumatoid arthritis (RA) and osteoarthritis (OA) remains obscure, although angiogenesis appears to play an important role. We recently confirmed an overexpression of two angiogenic factors, namely vascular endothelial growth factor (VEGF) and platelet-derived endothelial cell growth factor (PD-ECGF), by the lining and stromal cells of the synovium in both conditions. Because hypoxia inducible factor (HIF)-1alpha and HIF-2alpha are essential in regulating transcription of the VEGF gene, active participation of HIF-alpha molecules in the pathogenesis of these arthritides is anticipated. We investigated the immunohistochemical expression of HIF-1alpha and HIF-2alpha in the synovium of 22 patients with RA, 34 patients with OA and 22 'normal' nonarthritic individuals, in relation to VEGF, VEGF/KDR (kinase insert domain protein receptor) vascular activation, PD-ECGF and bcl-2. A significant cytoplasmic and nuclear overexpression of HIF-1alpha and HIF-2alpha was noted in the synovial lining and stromal cells of both diseases relative to normal. Overexpression of HIF-alphas was related to high microvessel density, high PD-ECGF expression and high VEGF/KDR receptor activation, suggesting HIF-alpha-dependent synovial angiogenesis in OA. By contrast, the activation of the angiogenic VEGF/KDR pathway was persistently increased in RA, as indeed was microvessel density and the expression of PD-ECGF, irrespective of the extent of HIF-alpha expression, indicating a cytokine-dependent angiogenesis. In all cases, the VEGF/KDR vascular activation was significantly lower in OA than in RA, suggesting a relative failure of the HIF-alpha pathway to effectively produce a viable vasculature for OA, which is consistent with the degenerative nature of the disease. The activation of the HIF-alpha pathway occurs in both RA and OA, although for unrelated reasons.